Assessment of the Cardiopulmonary Resuscitation Skills among the Students of Dentistry - Mawra Hyder, Talha Asher, Sadia Rashid, Syed Midhat Batool, Javeria Afzal, Asif Noor, Muhammad Rizwan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background Cardiopulmonary arrest (CPA) has been defined as “unpredicted & the quick halt/stop in the breathing of patients or/and circulation due to numerous reasons. Cardiopulmonary resuscitation incorporates complete hard work & the practices for the reviving of that individual/person who is in the heart failure. All of the wellbeing professionals, including oral/dental experts, have to be trained and prepared enough to oversee health linked crises. Aim: To see student’s skills of latest CPR guiding principles Study design: Cross-sectional study Place and duration of study: This study of 3 months duration was carried on students of Multan dental college Multan. Methodology: Eighty Students were chosen randomly. Knowledge concerning CPR was appraised by objective type printed paper. Practical skills/ expertise was then appraised by the SimMan (the high-fidelity simulator). The paper embraced of eighteen true false and 7 MCQ’s. Every query was of one mark and the passing score was 50%. Results: Men were thirty two while ladies were forty eight. 66(82.5%) participants failed in initial assessment, 72(90%) students reported failure due to compression rate error, 58(72.5%) subjects were failed due to ventilation rate error and 61(76.25%) students failed due to wrong hand position Conclusion: Level of the knowledge in addition to training concerning the medicinal emergencies of students is below and less than required standard. Hence, it is imperative to place the correct strategies & plans in place to fortify zones of weakness.